Peranan Guru dalam Pendidikan Inklusif di Pendidikan Anak Usia Dini - Siti Nuraini; Sudrajat Sudrajat; Shafa’ Annisa Puspasari (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Currently, the number of Children with Special Needs (ABK) continues to increase every year, making the role of teachers increasingly vital in providing inclusive education services in schools. This increase in the number of ABK requires teachers to have adequate competencies to provide education tailored to the needs of each child. In this context, inclusive education is crucial, as it provides opportunities for all children, including those with special needs, to learn together in the same environment. This study aims to analyze the role of teachers in the context of inclusive education in Early Childhood Education (PAUD). The method used in this study is qualitative with a narrative approach, conducted in several PAUD institutions in Malang. The results show that teachers have a very important role in inclusive education in PAUD. The role of teachers in question covers several aspects, including the ability to recognize Children with Special Needs (ABK), conduct initial assessments of student needs, and understand how to implement appropriate learning for ABK. In addition, teachers are also expected to be able to use assistive devices to provide simple stimulation to ABK and know how to involve parents in handling ABK. The importance of the teacher's role in inclusive education lies not only in academic abilities, but also in social and emotional skills in creating a supportive learning environment. This research provides valuable insights for the development of training programs for teachers to improve their skills in inclusive education, which is expected to have a positive impact on the quality of education in early childhood education (PAUD). With appropriate training, teachers can be better prepared to face the challenges of teaching children with special needs and ensure that every child receives a quality education tailored to their needs. This research is expected to encourage educational institutions to pay more attention to training and professional development for teachers, so they can contribute optimally to creating inclusive and quality education.